2021
DOI: 10.2147/opth.s323882
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Age-Related Retinal Vascular Changes in the Macula Using Optical Coherence Tomography Angiography of the Eyes After Cataract Surgery

Abstract: Purpose Optical coherence tomography angiography (OCTA) allows noninvasive observation of the retinal vasculature, and image analysis can be used to calculate the retinal vessel density and foveal avascular zone (FAZ) area. A previous study showed that macular vessel density and the signal strength index (SSI) of OCTA images increased significantly after cataract surgery. However, the effect of aging on OCTA analysis remains unclear. This study aimed to investigate age-related changes in macular v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Several studies have reported a significantly decreased in macular thickness and vessel density with age. 17,18 After adjusting for age, there were no significant differences in all parameters. This indicates that age is a very important factor affecting retinal thickness and vascular density.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Several studies have reported a significantly decreased in macular thickness and vessel density with age. 17,18 After adjusting for age, there were no significant differences in all parameters. This indicates that age is a very important factor affecting retinal thickness and vascular density.…”
Section: Discussionmentioning
confidence: 89%
“…Eye and Brain 2023: 15 [15][16][17][18][19][20][21][22][23] An ATD diagnosis is made based on clinical presentations by an experienced neurologist or neuropsychiatrist and confirmed only by a postmortem brain biopsy. 3 At the moment, non-invasive procedures that assist in the diagnosis of ATD have been gaining interest as novel diagnostic tools.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the algorithm might not have accurately identified the blood vessels in the OCTA images, and improvements are needed. However, it is known that OCTA measurements can be affected by various factors, such as the axial length, refractive error, and age ( 18 , 19 ), and our study compared the symmetrical retinal areas of the same eye. Thus, the effects of these factors were probably minor.…”
Section: Discussionmentioning
confidence: 99%